The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcb.28272
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves neurogenic bladder dysfunction through activation of NGF/TrkA signaling in a rat model

Abstract: Objective: To observe the effect of electroacupuncture on the morphological change of the bladder tissue and the protein expression levels of NGF, TrkA, p-TrkA, AKT, and p-AKT in the bladder tissue of rats with neurogenic bladder after suprasacral spinal cord injury and to preliminarily explore its partial mechanism of action. Methods: Eighty female Sprague-Dawley rats were randomly divided into blank group, model group, electroacupuncture group, model/siNGF group, and electroacupuncture/siNGF group according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…This result suggested successful modeling and indicated that NGF treatment had a certain recovery effect on neurons of spinal cord injury rats, which could further reduce the level of spinal cord injury in rats. The research conducted by the team of Zhang et al [20] shows that electroacupuncture can improve neurogenic bladder dysfunction by activating NGF/neurotrophin receptor (TrkA) signal transduction in rat model, which is similar to the results of this study. NGF is one of neurotrophic factors.…”
Section: Resultssupporting
confidence: 89%
“…This result suggested successful modeling and indicated that NGF treatment had a certain recovery effect on neurons of spinal cord injury rats, which could further reduce the level of spinal cord injury in rats. The research conducted by the team of Zhang et al [20] shows that electroacupuncture can improve neurogenic bladder dysfunction by activating NGF/neurotrophin receptor (TrkA) signal transduction in rat model, which is similar to the results of this study. NGF is one of neurotrophic factors.…”
Section: Resultssupporting
confidence: 89%
“…The maturation, plasticity, and survival of cholinergic neurons are inseparable from the nutritional support of NGF. NGF exerts physiological effects by binding to the TrkA or p75NTR receptor, while TrkA signaling inhibits apoptosis and promotes neuronal survival [49]; in contrast, the intracellular domain of p75NTR contains a "death domain, " and p75NTR overexpression facilitates neuronal apoptosis [2,14]. Therefore, we explored the effects of IHG and CHG on NGF receptors due to the close relationship between NGF receptors and neuronal apoptosis, and found that both IHG and CHG decreased TrkA level.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture (EA), which is a traditional Chinese medicinal therapy, has been widely used and applied during clinical practice and in animal models for the treatment of SCI 9–14 . The application of EA has been demonstrated to have neural protective and anti‐inflammatory effects, which would improve the suitability of the damaged areas for axonal regeneration after SCI.…”
Section: Introductionmentioning
confidence: 99%